Genetic Diversity in Echinococcus multilocularis From the Plateau Vole and Plateau Pika in Jiuzhi County, Qinghai Province, China - Li, Jian-qiu; Li, Li; Fan, Yan-lei; Fu, Bao-quan; Zhu, Xing-quan; Yan, Hong-bin; Jia, Wan-zhong (Frontiers in Microbiology, 2018)
Background: The Qinghai-Tibet Plateau is a highly endemic area of alveolar echinococcosis where a series of intermediate hosts, especially voles and pikas, are infected with Echinococcus multilocularis. The metacestodes of E. multilocularis are fluid-filled, asexually proliferating cysts, and they are mainly found in the host’s liver in the form of tumor-like growths. Methods: We investigated the genetic variations of E. multilocularis in four mitochondrial (mt) genes, namely, NADH dehydrogenase subunit 5 (nad5), adenosine triphosphate subunit 6 (atp6), cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1). The complete nad5, atp6, cox1 and nad1 genes were amplified separately from each hydatid cyst isolate using polymerase chain reaction (PCR) and then sequenced. Phylogenetic trees were then generated based on the combined mt genes using MrBayes 3.1.2 and PAUP version 4.0b10. Results: Thirty of 102 voles and two of 49 pikas were infected with E. multilocularis. The genetic variation distances among all E. multilocularis samples were 0.1-0.4%, 0.2-0.4%, 0.1-0.6%, and 0.1-0.4% for nad5, atp6, nad1 and cox1, respectively. Compared to previous studies of the genetic diversity of E. multilocularis based on the cox1 gene, the genetic distances within the same group were 1.3-1.7% (Mongolia strain), 0.6-0.8% (North American strain), 0.3-0.6% (European strain) and 0.1-0.4% (Asian strain). Based on concatenated sequences of the nad5, atp6, cox1 and nad1 genes all haplotypes were divided into two clusters. Conclusion: The genetic diversity of E. multilocularis based on mt genes on a local scale is low but in different regions, the genetic diversity is relatively high; genetic variation is higher in the nad1 gene than that in the other three mt genes. The results on a local scale provide basic information for further study of the molecular epidemiology, genetic differences and control of E. multilocularis in Qinghai Province, China.